Opportunistic prostate‐specific antigen testing in Norwegian men: a public health challenge - Albertsen, Peter C.; Bjerner, Lars Johan; Pasovic, Lara; Müller, Stig; Fosså, Sophie; Carlsson, Sigrid V.; Oldenburg, Jan (BJU international, 2024)
Objective To describe age‐specific prostate‐specific antigen (PSA) distributions and resulting prostate cancer diagnoses that arise from population‐wide opportunistic PSA testing. Patients and Methods Over 8 million PSA tests were performed on >1.4 million Norwegian men from 2000 to 2020. During this period 43 486 men were diagnosed with localised prostate cancer. Most of the PSA testing reflected opportunistic testing. Age‐specific PSA value distributions were constructed for men aged 45–75 years with and without prostate cancer. Results The distributions of PSA values in men with and without prostate cancer widened with age and overlapped extensively from 3 to 7 ng/mL. Localised prostate cancer diagnoses increased 10‐fold from the age of 45 to 75 years. PSA testing identified intermediate‐ or high‐grade cancers in 21% (95% confidence interval [CI] 19–23%) of men aged 50–54 years and 42% (95% CI 41–43%) of men aged 70–74 years. Grade group (GG)1, GG2, GG3 and ≥GG4 constituted 49%, 31%, 10% and 10% of cancers identified at age 50–54 years and 26%, 26%, 18%, and 30% of cancers identified at age 70–74 years. Conclusion Opportunistic PSA testing increases with ageing and often generates values that cannot discriminate benign prostate enlargement from prostate cancer. A clinical cascade using additional imaging or serum tests is necessary to avoid negative biopsies and the overdiagnosis of indolent disease. The declining specificity of PSA testing with ageing poses a significant public health challenge especially among older men aged ≥70 years.